Leveraging Interfacial Electric Field for Smart Modulation of Electrode Surface in Nitrate to Ammonia Conversion - Kouer Zhang; Yifan Xu; Fatang Liu; Qing Wang; Xiaohong Zou; Mingcong Tang; Michael K.H. Leung; Zhimin Ao; Xunhua Zhao; Xiao Zhang; Liang An (Advanced Science)
Abstract The efficiency of nitrate reduction reaction (NO3RR) at low nitrate concentration is predominantly hindered by the poor affinity of nitrate ions and competitive hydrogen evolution reaction (HER), particularly in neutral and acidic media. Here, an innovative strategy to leverage the interfacial electric field (IEF) is introduced to boost the NO3RR performance. By in situ constructing tannic acid‐metal ion (TA‐M2+) crosslinked structure on the electrode surface, the TA‐M2+‐CuO NW/Cu foam sample exhibits an exceptional Faraday efficiency of 99.4% at −0.2 V versus reversible hydrogen electrode (RHE) and 83.9% at 0.0 V versus RHE under neutral and acidic conditions, respectively. The computational studies unveil that the TA‐Cu2+ complex on the CuO (111) plane induces the increasing concentration of nitrate at the interface, accelerating NO3RR kinetics over HER via the IEF effect. This interfacial modulation strategy also contributes the enhanced ammonia production performance when it is employed on commercial electrode materials and flow reactors, exhibiting great potential in practical application. Overall, combined results illustrated multiple merits of the IEF effect, paving the way for future commercialization of NO3RR in the ammonia production industry.